PERBANDINGAN HASIL PENGGUNAAN METODE WP DAN TOPSIS PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI LAHAN TAMBAK PALING TERBAIK UNTUK DIJADIKAN USAHA TAMBAK AIR PAYAU - Yani Maulita; Relita Buaton (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2016)
The number of methods available to the decision support system, so sometimes confused to choose which one matches the use of the method according to the case of a decision support system. For that made a comparison of the case of a decision support system of pond site selection to be the best business brackish water ponds for the comparison of the decision. The method used is weighted product (WP) and TOPSIS by determining the number of criteria, the type of criteria (Cost and Benefits), with three alternatives. Results of the study is the result of manual calculation equal to the calculations in thesystem. Each of the calculation of the WP and TOPSIS methods show that the results in the selection of the best locations embankment land to be used as business brackish water ponds each method has different outcomes depending.